Magic lighters / Fatin Syakirah Rahmat … [et al.] - Rahmat, Fatin Syakirah; Mohammad Jamal, Nurul Amanina; Azmi, Noraina; Ahmad, Amaliana; Ismail, Nur Najihah; Asrul, Siti Aisyah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
The ability to take notes in an efficient manner is an essential skill for students of all ages, and the use of colourful highlighters can be an effective tool that significantly enhances the process. The use of highlighters not only makes it simpler to recall important information, but they also make the process of studying and reviewing notes more pleasurable. However, there will be times when students slip up and want to erase the area to start again. Notwithstanding, when students need to erase the highlighter ink due to mistakes or other reasons, this can be difficult and can cause more damage than good. Thus, in order to solve the issues of erasing the unintended highlighting the text on papers. we decided to develop a magic lighter where it can be deleted if students make a mistake on the note. Additionally, we prioritize the use of high-quality materials in our products. For instance, fluorescein, plastic cap, plastic barrel serves as a key component.